2021
DOI: 10.1002/cpt.2311
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between SNP Genotype and Efficacy of Anastrozole and Exemestane in Early‐Stage Breast Cancer

Abstract: Aromatase inhibitors (AIs) are the treatment of choice for hormone receptor-positive early breast cancer in postmenopausal women. None of the third-generation AIs are superior to the others in terms of efficacy. We attempted to identify genetic factors that could differentiate between the effectiveness of adjuvant anastrozole and exemestane by examining single-nucleotide polymorphism (SNP)-treatment interaction in 4,465 patients. A group of SNPs were found to be differentially associated between anastrozole an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It is an antigen-uptake receptor on dendritic cells [ 32 ]. In other studies, LY75 was found to participate in controlling cellular phenotypes in breast cancer and thus their metastatic potential [ 33 ]. Regarding environmental factors, DEC-205, together with IL-6 and CD86, was found to be predictive biomarker for respiratory and immune effects of particulate matter [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an antigen-uptake receptor on dendritic cells [ 32 ]. In other studies, LY75 was found to participate in controlling cellular phenotypes in breast cancer and thus their metastatic potential [ 33 ]. Regarding environmental factors, DEC-205, together with IL-6 and CD86, was found to be predictive biomarker for respiratory and immune effects of particulate matter [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific siRNAs that targeted RPP25 , EMP1 , EXTL3 , EXOC2 , NUP37 , RPL13 , WBP2NL , RPS6 , GBP1 , JAK2 , and negative siRNA controls (Horizon Discovery) were transfected into MCF7 and T47D cells in 96-well plates using Lipofectamine RNAiMAX Transfection Reagent (Catalog No. 13778500, ThermoFisher Scientific, Waltham, MA) according to the vendor’s protocol [67] , [83] . Total RNA was extracted 48 h after transfection for RNA quantification.…”
Section: Methodsmentioning
confidence: 99%
“…205 Aromatase inhibitors, such as anastrozole and exemestane, inhibit the conversion of androstenedione to estrone in breast cancer patients, thereby significantly reducing plasma estrogen levels to inhibit the proliferation of ER-positive breast tumors. 206 However, there are few studies on the relationship between lncRNAs and the function of aromatase inhibitors. Until now, only lncRNA MIR2052HG has been reported to be associated with breast cancer resistance to aromatase inhibitors.…”
Section: Lncrnas Mediate Breast Cancer Invasion and Metastasismentioning
confidence: 99%